Arthroscopic Stabilization of Posterior Shoulder Instability Without Glenoid Bone Loss - Shawn D. Feinstein MD; James M. Gregory MD (SAGE Publishing, 2022)
Background: Contact athletes who experience posterior shoulder instability have a high likelihood of recurrence necessitating surgery. Indications: Patients with posterior shoulder instability without glenoid or humeral head bone loss who have failed activity modification, bracing, and physical therapy may benefit from arthroscopic stabilization surgery. Technique Description: We describe a technique for arthroscopic labral repair with capsular plication through 4 portals in the lateral decubitus position. Results: Arthroscopic capsulolabral reconstruction is an effective and reliable treatment for posterior shoulder instability with good patient-reported outcomes, low recurrence rates, and high rate of return-to-play. Discussion/Conclusion: Arthroscopic capsulolabral reconstruction in the lateral decubitus position with appropriately placed portals allows for safe and effective repair of the labrum and capsular plication to address posterior shoulder instability. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.